The effect of pregnancy on peak expiratory flow rate in comparison with non-pregnant Iraqi women Sample in MARJAN Teaching Hospital - Al Janabi, Monqith A.; Mohamed Ameen, Ameerah J.; Ali Al-Eqabi, Dalya A. (Journal of the Faculty of Medicine Baghdad, 2016)
Background: Profound alterations of respiratory function physiology accompany pregnancy; these conditions contribute to many of the disorders of the lung during pregnancy. The adaptive changes during the gravid period are designed to support maternal and fetal well-being during the special stresses of fetal growth and parturition Peak. Objective: This study aimed to know the effect of pregnancy on peak expiratory flow rate in comparison with non-pregnant Iraqi women. Method: This study was conducted on 255 healthy female at their reproductive ages , made up of 60 pregnant female in 1st trimester , 65 in 2nd trimester , 60 in 3rd trimester and 70 non pregnant as control group. Results: There were a significant negative relation between PEFR % and gestational age. The PEFR % decrease progressively with advancing gestational age in comparison with control group (p< 0.001). Conclusion: These results suggest that the effect of pregnancy on the respiratory function of healthy women is influenced by gestational age.